REFORM OF CONTROL (SUPERVISION) ACTIVITIES IN THERUSSIAN FEDERATION: EXPERIENCE OF DIGITIZATION - STENKIN D.S. (Legal Bulletin)
Currently, digitalization of public administration is a global trend. Russia, as a country with a high level of digital development, is implementing very competitive and ambitious tasks, including within the framework of the reform of control and supervisory activities, which allows us to bring the provision of public services and government functions to a significantly new level. The relevance of the study is determined by the status of the Russian economy, as one of the largest economies in the world, the introduction of a comprehensive range of information systems and services aimed at ensuring a modern and effective system of government control and supervision, increasing the level of digital culture and literacy, reducing ineffective costs, reducing procedural deadlines, increasing Russian economy and business development. The main goal of the study is to study the experience of digital development of the control and supervision system in Russia as part of the ongoing reform of control and supervisory activities. The author of the study tries to answer the range of tasks of digitalization of control and supervision bodies, and also analyzes the information systems and digital services being implemented, giving relevant examples. In addition, the author examines the stages of the ongoing reform, the regulatory framework, explains and analyzes the mechanisms of digitalization, and provides current examples of the implementation of information systems, digital services and digital cloud solutions. Methods used. In this work, the following methods were used: general scientific (dialectical, analysis, synthesis) and special legal methods (comparative legal, formal legal). As conclusions, the results of the reform of control and supervisory activities are presented from the perspective of the experience of introducing digital processes in state control and supervision bodies, and an analysis of the results of the ongoing reform is provided.